THE GROWTH OF SEAWEED (Kappaphycus alvarezii) CULTIVATED WITH LONG LINE AND OFF BOTTOM METHOD ON TITA BANDA NEIRA MALUKU COASTAL AREA - Basir, Aditya Putra; Abukena, La; Amiludin, Mr. (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2017)
This research aimed to know the growth rate of seaweed (Kappaphycus alvarezii) cultivated by using off bottom method and long line method in coastal waters Tita Dwiwarna Village Banda Central of Maluku. It is expected that this research will provide basic information in business of seaweed cultivation to be developed. The methods were off bottom method and long line method that consisted of 2 treatments and 3 replications. Material used was mostly a polyethylene rope as long as 10 meters with the diameter size 5 mm for a mine rope and 3 mm for a span rope. Initial weight of sea weeds which is tied to a span rope 100 gram. The growth data collection was taken simultaneously with water quality data every week. Data were analyzed by using Cohran test to see homogeneity. The homogeneity data were then analyzed by using t-test to see the different between two treatments. The result of the research has shown that seaweed growth was highest in off bottom methods which average weight on the seventh week reached 690 gram. While the growth with long line methods reached the average weight on the seventh week reached only 609.4 gram. Therefore, the best growth of the sea weed was represented by off bottom method.